Use of near infrared femtosecond lasers as sub-micron radiation microbeam for cell DNA damage and repair studies. - Botchway, S; Reynolds, P; Parker, A; O'Neill, P (2010)
Laser induced radiation microbeam technology for radiobiology research is undergoing rapid growth because of the increased availability and ease of use of femtosecond laser sources. The main processes involved are multiphoton absorption and/or plasma formation. The high peak powers these lasers generate make them ideal tools for depositing sub-micrometer size radiant energy within a region of a living cell nucleus to activate ionising and/or photochemically driven processes. The technique allows questions relating to the effects of low doses of radiation, the propagation and treatment of deoxyribonucleic acid (DNA) damage and repair in individual live cells as well as non-targeted cell to cell effects to be addressed. This mini-review focuses on the use of near infrared (NIR) ca. 800nm radiation to induce damage that is radically different from the early and subsequent ultraviolet microbeam techniques. Ultrafast pulsed NIR instrumentation has many benefits including the ability to eliminate issues of unspecific UV absorption by the many materials prevalent within cells. The multiphoton interaction volume also permits energy deposition beyond the diffraction limit. Work has established that the fundamental process of the damage induced by the ultrashort laser pulses is different to those induced from continuous wave light sources. Pioneering work has demonstrated that NIR laser microbeam radiation can mimic ionising radiation via multiphoton absorption within the 3D femtolitre volume of the highly focused Gaussian beam. This light-matter interaction phenomenon provides a novel optical microbeam probe for mimicking both complex ionising and UV radiation-type cell damage including double strand breaks (DSBs) and base damage. A further advantage of the pulsed laser technique is that it provides further scope for time-resolved experiments. Recently the NIR laser microbeam technique has been used to investigate the recruitment of repair proteins to the sub-micrometre size area of damage in viable cells using both immuno-fluorescent staining of gamma-H2AX (a marker for DSBs) and real-time imaging of GFP-labelled repair proteins including ATM, p53 binding protein 1 (53BP1), RAD51 and Ku 70/80 to elucidate the interaction of the two DNA DSB repair pathways, homologous recombination and the non-homologous end joining pathway.